Overall variation of the H2O masers around W Hydrae in 28 years. (16th October 2019) - Imai, Hiroshi; Nakagawa, Akiharu; Takaba, Hiroshi
Abstract: In this paper, we present the distribution of H_2 O masers associated with the semi-regular variable star W Hydrae (W Hya). We have collected the radio interferometric data of the maser distribution taken with the Very Large Array (VLA), the Kashima–Nobeyama InterFErometer (KNIFE), the Multi-Element Radio Link Network (MERLIN), the VLBI Exploration of Radio Astrometry (VERA), and the combined array of the Korean VLBI Network (KVN) and VERA (KaVA) in order to trace the maser distribution variation in two decades. Even though differences in the sensitivities and angular resolutions of the interferometric observations should be taken into account, we attempt to find possible correlation of the maser distribution with the stellar light curve. Our failure in the measurement of the annual parallax of the masers with VERA is likely caused by the properties of the maser features, which have been spatially resolved by the synthesized beam and survived for only half a year or less. No dependence of the maser spot flux density on its size is found in the KNIFE data, suggesting that maser spot size is determined by the physical boundary, as is expected for a clump affected by outward propagation of a stellar pulsation shock wave, rather than the (spherical) geometry of maser beaming in the maser gas clump.